Extracellular proteases are key mediators of Staphylococcus aureus virulence via the global modulation of virulence‐determinant stability. Issue 1 (11th December 2012) - Kolar, Stacey L.; Antonio Ibarra, J.; Rivera, Frances E.; Mootz, Joe M.; Davenport, Jessica E.; Stevens, Stanley M.; Horswill, Alexander R.; Shaw, Lindsey N.
Abstract Staphylococcus aureus is a highly virulent and successful pathogen that causes a diverse array of diseases. Recently, an increase of severe infections in healthy subjects has been observed, caused by community‐associated methicillin‐resistant S. aureus (CA‐MRSA). The reason for enhanced CA‐MRSA virulence is unclear; however, work suggests that it results from hypersecretion of agr‐regulated toxins, including secreted proteases. In this study, we explore the contribution of exo‐proteases to CA‐MRSA pathogenesis using a mutant lacking all 10 enzymes. We show that they are required for growth in peptide‐rich environments, serum, in the presence of antimicrobial peptides (AMPs), and in human blood. We also reveal that extracellular proteases are important for resisting phagocytosis by human leukocytes. Using murine infection models, we reveal contrasting roles for the proteases in morbidity and mortality. Upon exo‐protease deletion, we observed decreases in abscess formation, and impairment during organ invasion. In contrast, we observed hypervirulence of the protease‐null strain in the context of mortality. This dichotomy is explained by proteomic analyses, which demonstrates exo‐proteases to be key mediators of virulence‐determinant stability. Specifically, increased abundance of both secreted (e.g. α‐toxin, Psms, LukAB, LukE, PVL, Sbi, γ‐hemolysin) and surface‐associated (e.g. ClfA+B, FnbA+B, IsdA, Spa) proteins was observed upon protease deletion. Collectively, our findings provide a unique insight into the progression of CA‐MRSA infections, and the role of secreted proteolytic enzymes.